The Effect of Toe-Only Rocker Sole at 10-Degree’s Extension on Dynamic Balance in Transtibial Prosthesis Users - Suprayogi, Dody; Nugroho, Agus Setyo (Poltekkes Kemenkes Jakarta I, 2023)
Background: For transtibial amputees, the use of a transtibial prosthesis has an impact on balance during daily activities (Wang et al., 2015). Apart from the prosthesis which affect walking patterns and balance, the use of the shoes related to the patient's balance. Modifications to the shoes of transtibial prosthesis users to achieve the best balance with toe-only rocker sole are considered an option to improve balance (Preece et al., 2017). Objective: To determine the effect of a 10-degree toe-only rocker sole on dynamic balance in transtibial prosthesis users. Methods and Subjects: This research was conducted from May to June in APOC Boyolali, using a quantitative research method using a quasi-experimental one group pre-test and post-test design. The sampling technique used is purposive sampling. The subjects used were transtibial prosthesis users. Results: A Statistical analysis with a p value of 0.000 less than 0.05 revealed that the use of a toe only rocker sole of 10 degrees had an impact on dynamic balance in transtibial prosthesis users. Conclusion: There is an effect of using a 10-degree toe only rocker sole to improve the dynamic balance of transtibial prosthesis users, so that reducing the risk of falls when carrying out daily activities.